Exotic Moscow under Western Eyes - Masing-Delic, Irene (Cultural Revolutions: Russia in the Twentieth Century, 2009)
This collection of essays on Turgenev, Goncharov, Conrad, Dostoevsky, Blok, Briusov, Gor'kii, Pasternak and Nabokov represents diverse voices but is also unified. One invariant is the recurring distinction between "culture" and "civilization" and the vision of Russia as the bearer of culture because it is "barbaric." Another stance advocates the synthesis of "sense and sensibility" and the vision of "Apollo" and "Dionysus" creating a "civilized culture" together. Those voices that delight in the artificiality of civilization are complemented by those apprehensive of the dangers inherent in barbarism. This collection thus adds new perspectives to the much-debated opposition of vital Russia and a declining West, offering novel interpretations of classics from Oblomov to Lolita and The Idiot to Doctor Zhivago.